Medicare's National Coverage Decisions For Technologies, 1999-2007 - Neumann, Peter J; Kamae, Maki S; Palmer, Jennifer A (Health Affairs, 2008)
An analysis of Medicare national coverage decisions (NCDs) from 1999 through 2007 reveals that the Centers for Medicare and Medicaid Services (CMS) considers the available evidence as no better than fair for most of the technologies considered. Still, the CMS issues favorable decisions in 60 percent of the cases it takes on, although almost always with conditions placed on coverage. Since enactment of the 2003 Medicare Modernization Act, which legislated maximum review times for NCDs, the CMS has eliminated "long duration" decisions (more than one year) and has issued several "coverage with evidence development" decisions, which promise flexibility but also carry implementation challenges.